Study of Ophidian Faunal Diversity in Amravati Region of Maharashtra, India (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
India is also known as the ‘Land of Snakes’. as there are Out of venomous species main are Cobra, Russell’s Viper, Saw Scaled Viper , and Krait, the remaining species are either semi-venomous or non-venomous. But still most people are afraid of snakes as they don’t know much about them, is the prime reason for decline of this fascinating creature. Vidarbha has an arid topography with high temperatures, and other climatic conditions that favour the reptilian fauna. Very few researcher studied snakes diversity in Vidarbha, and hence there is a need to study ophidian fauna. The specimens were observed during the visit of the probable habitats or the rescuers associated with different NGOs, photographed, and identified with the help of keys, and methods suggested by Daniel (2002) Whitaker, and Captain (2004) , and Khaire (2010).In the present study, diversity of this ophidian fauna is identified, and found six families of snakes namely Typhlopidae, Pythonidae, Boidae, Colubridae, Elapidae, , and Viperidae , and represent 19 species. Out of the total identified species four venomous snakes, thirteen non-venomous, and two semi- venomous are reported during the month from August 2018 to March 2019. The habitats, and other ecological parameters along with the existence of ophidian form we can correlate in the future part of the study.